2020
DOI: 10.3390/pharmacy8010031
|View full text |Cite
|
Sign up to set email alerts
|

The Prescribing and Education of Naloxone in a Large Academic Medical Center

Abstract: The opioid epidemic has led to increased needs for opioid reversal agents which require education and counseling for proper use. The purpose of this study was to evaluate outpatient naloxone prescribing and education practices at an academic medical center to understand the current state and inform quality improvement measures. This retrospective chart review study included 439 patients that were at least 18 years old and received an outpatient prescription for naloxone between 1 July 2017 and 30 June 2018. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…[35]. Although the majority of pharmacies from one study perceived to have an area in their pharmacy that is HIPAA compliant, about 23% of pharmacies did not have a semi-private area for patient counseling [34]. This could contribute as a barrier to patient education.…”
Section: Outcomes Of Pharmacist Contributionsmentioning
confidence: 99%
“…[35]. Although the majority of pharmacies from one study perceived to have an area in their pharmacy that is HIPAA compliant, about 23% of pharmacies did not have a semi-private area for patient counseling [34]. This could contribute as a barrier to patient education.…”
Section: Outcomes Of Pharmacist Contributionsmentioning
confidence: 99%
“…79 This was far behind indications involving prescription opioid use, totaling 39.9% (concomitant benzodiazepine use, opioid use, or MME>50, constituting 21.9%, 13.9%, and 4.1% respectively, of documented indications for naloxone prescriptions). 79 Taken together, these studies suggest that most patients prescribed naloxone are high-risk prescription opioid users who are neither OUD patients, nor the so-called “drug addicts” whose stereotypes may be projected on every naloxone prescription recipient. However, an important consideration is that this stereotyped group may disproportionately influence public perception about naloxone and those to whom it is prescribed.…”
Section: To What Extent Is the Attitude Toward Naloxone Affected By T...mentioning
confidence: 99%
“…78 A study conducted in a large academic medical center reported that only 14.3% of naloxone prescriptions were for the combined indications of a history of overdose and substance abuse. 79 This was far behind indications involving prescription opioid use, totaling 39.9% (concomitant benzodiazepine use, opioid use, or MME>50, constituting 21.9%, 13.9%, and 4.1% respectively, of documented indications for naloxone prescriptions). 79 Taken together, these studies suggest that most patients prescribed naloxone are high-risk prescription opioid users who are neither OUD patients, nor the so-called "drug addicts" whose stereotypes may be projected on every naloxone prescription recipient.…”
Section: Is Oud the Only Cause And Driver Of Naloxone Stigma?mentioning
confidence: 99%